EKSPLORASI PERAN FRAUD PENTAGON THEORY DALAM MENDETEKSI FRAUDULENT FINANCIAL REPORTING - Erika Della Saputri; Ety Meikhati; Putri Intan Prastiwi (Universitas Duta Bangsa Surakarta, 2025)
This study aims to examine the influence of elements in the Fraud Pentagon Theory consisting of pressure, opportunity, rationalization, ability, and arrogance on fraudulent financial reporting. This study uses a quantitative approach with primary data obtained through distributing questionnaires to 80 respondents who are financial staff and auditors in the Surakarta area. The data analysis technique used is multiple linear regression with the help of SPSS software version 27. The results of the analysis show that the variables of opportunity, rationalization, ability, and arrogance have a significant effect on fraudulent financial reporting, while pressure has no effect on fraudulent financial reporting.